REFLECTION OF THE ADOPTION OF INTERNATIONAL FINANCIAL REPORTING STANDARDS IN THE AUDIT EVIDENCE METHODOLOGY - Amna laith hazim; Asst. Prof.dr. Iman Shakir mohammed (Scholar Express Journals, 2022)
This research aims to demonstrate the reflection of the adoption of international financial reporting standards on the methodology of evidence in external auditing and to clarify the role played by the external auditor by collecting and evaluating evidence in terms of quantity and quality in accordance with international financial reporting standards to express a technical and neutral opinion on the financial statements. The adoption of international financial reporting standards in the methodology of proof in auditing, through an exploratory study of the opinions of a sample of academics and professionals, and the research problem represents what is the impact of the adoption of financial reporting standards IFRS on the evidence methodology in external audit, and does the evidence differ in light of the adoption of international financial reporting standards IFRS . Where the research was based on the following basic hypothesis: There is no significant relationship between the adoption of international financial reporting standards and the methodology of evidence in the external audit. From which the following sub-hypothesis: First sub-hypothesis: there is no significant relationship between the adoption of international financial reporting standards and the evidence methodology. In the external audit. And the second sub-hypothesis: There is no significant effect relationship between the adoption of international financial reporting standards and the methodology of evidence in the external audit.
Keywords: international financial reporting standards,; Evidence methodology